2013
DOI: 10.1371/journal.pone.0072329
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Sigma Factor Competition in the Regulation of Alginate Production by Pseudomonas aeruginosa

Abstract: Alginate overproduction, or mucoidy, plays an important role in the pathogenesis of P. aeruginosa lung infection in cystic fibrosis (CF). Mucoid strains with mucA mutations predominantly populate in chronically-infected patients. However, the mucoid strains can revert to nonmucoidy in vitro through suppressor mutations. We screened a mariner transposon library using CF149, a non-mucoid clinical isolate with a misssense mutation in algU (AlgUA61V). The wild type AlgU is a stress-related sigma factor that activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…SspA orthologs from several other bacteria, including Neisseria gonorrhoeae (16), Yersinia enterocolitica (17), Vibrio cholerae (18), enterohemorrhagic E. coli (20), and Pseudomonas aeruginosa (19), have also been implicated in regulating virulence gene expression. The mechanism by which SspA regulates the expression of virulence genes in these other organisms, however, is currently not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SspA orthologs from several other bacteria, including Neisseria gonorrhoeae (16), Yersinia enterocolitica (17), Vibrio cholerae (18), enterohemorrhagic E. coli (20), and Pseudomonas aeruginosa (19), have also been implicated in regulating virulence gene expression. The mechanism by which SspA regulates the expression of virulence genes in these other organisms, however, is currently not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…SspA orthologs in several other pathogens have also been shown to be important for virulence (16)(17)(18)(19)(20). F. tularensis genes encode two orthologs of SspA, one called MglA and another that is called SspA.…”
mentioning
confidence: 99%
“…One other possible explanation for the altered ttgABC gene expression in the ECF-10 knockout mutant could be sigma factor competition for the core RNA polymerase. This phenomenon has been shown to be responsible for altered regulation of genes or even whole pathways in various bacteria, including Pseudomonas aeruginosa and E. coli, among many others (54,55). Although the ECF sigma factor RpoT (ECF-12) was identified to control the ttgGHI efflux pump genes in P. putida DOT-T1E (56), so far, no sigma factor has been described to be involved in ttgABC transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate production in PAO1 and clinical isolates was significantly decreased after zingerone treatment. Alginate producing mucoid P. aeruginosa strains were typically associated with chronic pulmonary infections (Pedersen et al, 1992;Yin et al, 2013) and it has been shown that mucoid alginate-producing mutants of P. aeruginosa are major pathogens in patients with cystic fibrosis (Govan et al, 1992). Reversion of mucoid to non-mucoid phenotype is common in vitro and in vivo during the end-stage of CF disease that has been linked to environment pressure leading to decreased progression of infection (Yin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%